Pengaruh Digitalisasi Pada Peningkatan Efisiensi Operasional Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia Tahun 2023 - Mendrofa, Lustantri; Zendrato, Bowoaro; Zai, Iperusman (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
The research examines the impact of digitalization on the operational efficiency of micro, small, and medium enterprises (MSMEs). Using both qualitative and quantitative approaches, this study explores how adopting digital tools influences productivity, reduces costs, and improves competitiveness. Data was collected through surveys, interviews, and case studies across 100 MSMEs in Indonesia. Findings indicate that digitalization significantly enhances operational efficiency by 45%, particularly in inventory management and customer engagement. This paper highlights the critical need for capacity building and access to digital infrastructure for MSMEs to fully capitalize on digitalization benefits.